(untitled) (Revista Rupturas, 2024)
haped by processes of urbanization and development, which have led to impacts, both positive and negative, at local, regional and global levels. The aim of this document is to describe the aspects that sustainability in cities implies, in order to understand the challenges and perspectives in Costa Rica. Costa Rican cities are lagging behind in terms of sustainability. These include the development of a broad and integrated approach, to encompass and seek sustainability for the Greater Metropolitan Area. In order to guide the country’s cities towards sustainability, it is necessary to leave behind the short-sighted and individualistic vision, to promote integrated and innovative solutions that meet the country’s needs.